Identification of altered metabolic functional components using metabolomics to analyze the different ages of fruiting bodies of Sanghuangporus vaninii cultivated on cut log substrates - Xu, Congtao; Zhao, Shuang; Li, Zihao; Pan, Jinlong; Zhou, Yuanyuan; Hu, Qingxiu; Zou, Yajie (Frontiers in Nutrition, 2023)
Sanghuangporus vaninii is a profitable traditional and medicinal edible fungus with uncommonly therapeutic properties and medicinal value. The accumulation of active ingredients in this fungus that are used in traditional Chinese medicine is affected by the years of growth, and their pharmacological activities are also affected. However, the effects of age on the medicinal value of fruiting bodies of S. vaninii cultivated on a cut log substrate remain unclear. In this study, an untargeted liquid chromatography mass spectrometry (LC-MS)-based metabolomics approach was performed to characterize the metabolite profiles of three samples from 1-, 2-and 3-year-old fruiting bodies of S. vaninii. In total, 156 differentially accumulated metabolites (DAMs) were screened based on the criterion of a variable importance projection (VIP) greater than 1.0 and p<0.01, including 75% up-regulated and 25% down-regulated. The results of enrichment of metabolic pathways showed that these metabolites involved the biosynthesis of plant secondary metabolites, biosynthesis of amino acids, central carbon metabolism in cancer, steroid hormone biosynthesis, linoleic acid metabolism, prolactin signaling pathway, and arginine biosynthesis. The biosynthesis of plant secondary metabolites pathway was significantly activated. Five metabolite were significantly elevated within the growth of fruiting bodies, including 15-keto-prostaglandin F2a, (4S,5R)-4,5,6-trihydroxy-2-iminohexanoate, adenylsuccinic acid, piplartine, and chenodeoxycholic acid. 15-keto-prostaglandin F2a is related to the pathway of arachidonic acid metabolism and was significantly increased up to 1,320-and 535-fold in 2-and 3-year-old fruiting bodies, respectively, compared with those in the 1-year-old group, the existence of these bioactive natural products in S. vaninii is consistent with the traditional use of S. vaninii, which prompted the exploration of its use as a source of natural prostaglandin in the form of foods and nutraceuticals. This finding may provide insight into the functional components of S. vaninii to develop therapeutic strategies.